PENGARUH METODE GLOBAL TERINTEGRASI MODEL PEMBELAJARAN MAKE A MATCH TERHADAP KETERAMPILAN MEMBACA PERMULAAN SISWA KELAS II SD NEGERI 7 PANGKALANBARU - Putri Ades; Sasih Karnita Arafatun; Silvio Juliana Nabela (Universitas Negeri Surabaya, 2026)
This research was motivated by the low level of students' initial reading skills. Based on the problems that occur, it is known that students are still unable to pronounce clearly consonant letters (R, S, L) and combinations of letters (Ng, Ny, Sy). This research aims to determine whether there is an influence of the integrated global method of the make a match learning model on the beginning reading skills of class II students. This research uses quantitative research methods with the Pre-Experimental One Group Pretest Posttest Design research type. The results of the research show that the integrated global method, the make a match learning model, has an effect on the beginning reading skills of class II students. Judging from the results of the hypothesis test obtained from the paired sample test with a value of 0.000 < 0.05, it can be said that Ho is rejected and Ha is accepted. Based on this, it can be concluded that the integrated global method, the make a match learning model, has an influence on the beginning reading skills of class II students at SD Negeri 7 Pangkalanbaru.